Evaluating the Psychometric Properties of the Exercise Dependence Scale-Revised (EDS-R) in a Spanish Sample - Pujals, Constanza; Baile, José Ignacio; González Calderón, María José (Pensando Psicología, 2018)
Introduction: There are several instruments to evaluate behavioural addictions. Furthermore, several specific scales have been developed to assess various aspects of exercise dependence. Nevertheless, in Spain there is a lack of specific instruments designed to assess exercise dependence.Objective: This study aims to examine the psychometric properties of a Spanish version of the Exercise Dependence Scale-Revised.Method: 175 university students who were regular exercisers (M=59.11, SD=15.89) took part in the study. They were requested to complete the EDS-R, as well as the General Addiction Scale. The requirement to take part in the study was to exercise a minimum of four times per week.Results: Findings provide initial support for the psychometric properties of the scale as its internal consistency (Cronbach’s alpha: 0.907), and construct and convergent validity with the EAG-RC (r=.559; p
Keywords: EDS-R; exercise dependence; factor analysis; psychometric properties